Sobre dos especies argentinas de Batrachoididae (Pisces Batrachoidiformes) - Menni, Roberto Carlos (1976)
This paper iucluds comments on the genus Triathalassothia Fowler, 1943 and a redescription of T. argentina based in morphometrical data of a relatively large sample. Porichthys porosissimus from Argentine and southern Brazil is defined considering Rio de Janeiro as its northern limit and extending its range up to Golfo de San Matías. The otoliths morphology of both species is discussed.